Sarcopenia and Risk of Cognitive Impairment: Cohort Study and Mendelian Randomization Analysis - Tingting Sha; Yuqing Zhang; Jie Wei; Changjun Li; Chao Zeng; Guanghua Lei; Yilun Wang (JMIR Aging)
Abstract BackgroundOver half the people over 60 years of age experience cognitive impairment, with limited treatment options, making it crucial to identify risk factors. Studies have examined the association between sarcopenia and cognitive impairment; however, the evidence is inconclusive and cannot be used to make causal inferences. ObjectiveThis study aims to appraise the causal association of sarcopenia with cognitive impairment by triangulating the data from a cohort study and Mendelian randomization (MR) analysis. MethodsUsing UK Biobank data, we first examined the associations of sarcopenia and its indices (appendicular lean mass [ALM], handgrip strength, and gait speed) with cognitive function (fluid intelligence and prospective memory) by using mixed-effects regression models. Then, we explored the causal associations of genetically predicted sarcopenic indices with cognitive function through a 2-sample MR, and examined potential mediation by omega-3 fatty acids, vitamin D levels, physical inactivity, falls, frailty, sleep disorders, anxiety, depression, stroke, metabolic syndrome, and type 2 diabetes. ResultsA total of 34,457 participants, with a mean age of 56.4 (SD 7.6) years, 51.1% (n=17,620) of which were female, completed baseline cognitive tests between 2006 and 2010 and attended at least 1 follow-up visit in 2012, 2014, or 2019, and were included in the observational analysis. The cohort study revealed that sarcopenia was significantly associated with cognitive impairment, which was evidenced by reduced fluid intelligence scores (β=−0.91, 95% CI −1.68 to −0.15; PPPPP ConclusionsOur study suggests that sarcopenia is a potential causal risk factor for cognitive impairment, with physical activity acting as a modifiable mediator in this relationship.